2019
DOI: 10.1088/1755-1315/292/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Derris elliptica (Wall.) Benth Root Extract Against Temephos-resistant Aedes aegypti Larvae

Abstract: Derris elliptica (Wall.) Benth is a wild plant or weed in agricultural fields that was traditionally used for poisoning fish and plant pests. Several studies showed the low lethal concentration of Derris elliptica root extract to control the laboratory strain Aedes aegypti larvae. This study aimed to evaluate the effectiveness of Derris elliptica root extract against the temephos-resistant Aedes aegypti larvae from the Dengue endemic areas. This experimental study used post-test only control group design with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
6
1
1
Order By: Relevance
“…This extract also had a higher larvicidal potential against F2 offspring larvae of Cypermethrin-resistant Ae. aegypti rather than the temephos-resistant offspring ( 18 ). The larvicidal activity of this extract was also better than the methanolic extract of M. glaziovii peel ( 22 ), A. pinata ( 23 ), T. patula ( 24 ), H. forskaolii ( 25 ), O. campechianum and O. quixos ( 26 ), and A. occidentale ( 27 ) against the third-instar larvae of Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This extract also had a higher larvicidal potential against F2 offspring larvae of Cypermethrin-resistant Ae. aegypti rather than the temephos-resistant offspring ( 18 ). The larvicidal activity of this extract was also better than the methanolic extract of M. glaziovii peel ( 22 ), A. pinata ( 23 ), T. patula ( 24 ), H. forskaolii ( 25 ), O. campechianum and O. quixos ( 26 ), and A. occidentale ( 27 ) against the third-instar larvae of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies showed that ethyl acetate, methanol, and n-hexane extracts of D. elliptica that have different polarity effectively killed Ae. aegypti larvae which were susceptible to temephos 0.02ppm ( 17 ), but on the other hand, the ethanol extract type has a lower effect against the temephos-resistant strains ( 18 ). The lethal effects of different specific phytochemicals contained in D. elliptica root extracts against the offspring larvae of the cypermethrin-resistant strain Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Tanaman tuba telah dikenal luas pemanfaatannya sebagai racun untuk menangkap ikan, pestisida alami, dan pembunuh serangga vektor penyakit (Asmaliyah et al, 2010;Kinansi et al, 2018;Sumarmin, 2016). Senyawa kimia beracun yang ditemukan pada ekstrak akar tuba, terutama berasal dari golongan flavonoida seperti rotenone, toxicarol, elliptone, sumatrol, tephrosin, dan deguelin (Sayono, 2019). Senyawa aktif rotenone diketahui manfaatnya sebagai bioinsektisida, dan memiliki efektivitas lebih baik dibanding senyawa aktif lain dalam ekstrak akar tuba (Zubairi et al, 2014).…”
Section: Tuba (D Elliptica L)unclassified
“…Benth. root extract have larvacidal potential to control the temephos-resistant Aedes aegypti larvae (Sayono & Sumanto, 2019).…”
Section: Effect Of Derris Elliptica (Wall) Benth Against Temephos-resistant Aedes Aegypti Larvaementioning
confidence: 99%